OPTIMALISASI BUDAYA LITERASI MELALUI KOMUNITAS SASTRA ANAK DI SDK RUTENG 3, KECAMATAN LANGKE REMBONG, KABUPATEN MANGGARAI, NUSA TENGGARA TIMUR - Angela Klaudia Danu (Unika Santu Paulus Ruteng, 2019)
Optimization of Literacy Culture through Children's Literature Community in SDK Ruteng 3 Langke Rembong, Manggarai, East Nusa Tenggara. The community service activities aim to optimize the literacy culture of reading and writing for students and students of SDK Ruteng 3. The subject and object of this service activity are school residents, principals, teachers, employees and students in SDK Ruteng 3. Meanwhile, the object of activity is perception, the activities and behavior of school citizens against literary literacy activities. The method of implementing this service activity is through strategic stages along with intensive assistance from the child literature ca re community (PEDUS). The stages of service activities in general are as follows. lecturer together with community students form a literary care group (Poetry) in partner schools and hold regular poetry writing training on a regular basis, the student work will be published on the partner school's wall magazine. The next stage, rearranging the library is comfortable, safe, child-friendly, fun, and safe, applying the obligation to read 10 minutes every day, reading corners, make wall magazines of partner schools, holding the best reader, organizing poetry writing competitions, and making poetry ontology on the work of students at partner schools. The results of this service activity show that there is a significant increase and change in learning climate.